Pengembangan RPP Inovatif Abad 21 Pada Pembelajaran Tematik di Kelas IV SD Negeri Kota Bengkulu - Ayu Wulandari; Osa Juarsa; Neza Agusdianita (JURIDIKDAS, 2020)
This study aims to develop an innovative 21st century lesson plan (RPP) in grade IV elementary schools that can be used as a reference for teachers in implementing classroom learning. This study is a Research and Development (R&D) research by modifying the 4D model by Thiagarajan and Sammel. The development procedure consists of three stages, namely, define, design and develop. The validation was carried out by PGSD lecturers and elementary school teachers. The lesson plans developed were given scores and responses by 2 teachers to assess the products developed from the presentation and material aspects. The instrument used is in the form of a validation sheet to obtain input in the form of comments, assessments, notes, criticisms and suggestions for the initial draft lesson plans and teacher response questionnaires to collect data about teacher responses to the lesson plans that have been developed.The data were analyzed using qualitative descriptive analysis and descriptive statistics, namely expert validation data analysis and teacher response data analysis. Teacher responses obtained results of 89.285 with very good category as the final product of development. This research produces a development product in the form of innovative 21st Century RPP Keywords: Development, 21st Century Innovative RPP, Thematic